Comparison of Ground Reaction Forces, Center of Pressure and Body Center of Mass Changes in the Voluntary, Semi-Voluntary and Involuntary Gait Termination in Healthy Young Men - behrooz teymourian; heydar sadeghi; mohammad shariatzade joneydi (Islamic Azad University, Hamedan Branch, 2016)
Objective: The aim of this study was comparing the ground reaction forces, center of pressure and body center of mass changes in voluntary, semi-voluntary and involuntary gait termination in healthy young men. Methods: In this study, 12 young men performed termination of gait in three different patterns. The variable of peak antero-posterior and vertical forces in two directions at both limbs, the time to reach peak and average forces in every limb in both directions, the center of pressure displacement of medio-lateral and antero-posterior direction for each limb and the net center of pressure and the displacement of the center of mass motion in all three motion plates were recorded using motion analysis system and force plate.The repeated measurements test was used to compare three patterns of gait termination at significance level of p&le0.5. Results: The results showed a significant difference in variables of peak antero-posterior force, the time to reach peak antero-posterior force and mean antero-posterior forces of the leading limb, the peak antero-posterior force of the trialing limbs, the depth force of leading limbs, medio-lateral cop of leading limbs displacement and vertical displacement of the center of mass, among different patterns of gait termination. Conclusion: While walking, the probability of a fall or collision damage, when a sudden or unexpected stop is required, increases. Therefore, more coordination between neuromuscular systems is required.